(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Our density functional theory (DFT)/time-dependent DFT (TDDFT) calculations for the sensing mechanism of a series of sulfoxide based metal-responsive fluorescent chemosensors, suggested that the intramolecular charge transfer (ICT) is not a reasonable mechanism for these chemosensors. The calculated electronic transition energies, the corresponding oscillator strengths of these chemosensors and the involving frontier molecular orbital analysis indicated that there is no obviously ICT state with a transition oscillator strength approaching to zero. The fluorescence quenching of these chemosensors cannot be explained by ICT process. The ground state optimized structures of chemosensors and their complexes indicated that there might be twisted excited configuration for these chemosensors and the twisted excited state configuration may response for the fluorescence quenching. The configuration change can be blocked in the Zn complex that is responsible for these complexes showing fluorescence emission enhancement. In order to understand the function of the sulfoxides group in these metal-responsive fluorescent chemosensors, excited state configuration optimization as well as the excited state hydrogen bond effect on the fluorescence enhancement in the aqueous solvent will be conducted.